2001
DOI: 10.1007/s00468-001-0135-5
|View full text |Cite
|
Sign up to set email alerts
|

Implications of mucilage on pressure bomb measurements and water lifting in trees rooting in high-salinity water

Abstract: Various studies on mangroves and other tall trees rooting in high-salinity water have given compelling evidence that tension is not the only factor in water lifting as thought by plant physiologists. A characteristic feature of these trees is that the tissue cells, the apoplastic space and, in particular, the lumen and the inner walls of many xylem vessels of the roots, the trunk and the branches (up to the apex) contain mucilage. Data on single marine giant algal cells are presented that show that mucilage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 56 publications
(77 reference statements)
1
44
0
Order By: Relevance
“…Accumulation of mucilage in xylem vessels is an important strategy of Trees mangrove trees to save water. The viscous, polymeric substances in the xylem sap limit the rate of water flow and decrease transpiration (Zimmermann et al 1994(Zimmermann et al , 2002. Combined with high water-use efficiency this mechanism slows the rate of water uptake and prevents salts from accumulating in the soil surrounding the roots.…”
Section: Salinity Balancementioning
confidence: 99%
“…Accumulation of mucilage in xylem vessels is an important strategy of Trees mangrove trees to save water. The viscous, polymeric substances in the xylem sap limit the rate of water flow and decrease transpiration (Zimmermann et al 1994(Zimmermann et al , 2002. Combined with high water-use efficiency this mechanism slows the rate of water uptake and prevents salts from accumulating in the soil surrounding the roots.…”
Section: Salinity Balancementioning
confidence: 99%
“…These mucopolysaccharides in the xylem sap are apparently involved in water transport in the xylem conduit of R. mangle (Zimmermann et al 1994). Accumulation of mucilage in xylem vessels is an important strategy of mangrove trees to save water on its tortuous pathway to the uppermost crown (Zimmermann et al 1994(Zimmermann et al , 2002. The viscous, polymeric substances in the xylem sap limit flow rate and decrease transpiration (Zimmermann et al 1994(Zimmermann et al , 2002.…”
Section: Physiological and Biochemical Mechanismsmentioning
confidence: 99%
“…This effect is known to exist in electroosmotic flow and, although electro-osmotic flow is not under consideration here, the adhesion of the positive cations to the walls may still be relevant. Zimmermann U. et al (2002bZimmermann U. et al ( , 2004 have identified layers of mucilage adjacent to the xylem walls. This mucilage may be a consequence of damage to the xylem, as some physiologists maintain (e.g.…”
Section: A Charge Separation Due To Bound Charge On the Xylem Wallsmentioning
confidence: 99%